Determinants of Adoption and the Type of Solar PV Technology Adopted in Rural Pakistan - Ahmar, Muhammad; Ali, Fahad; Jiang, Yuexiang; Wang, Yichu; Iqbal, Kashif (Frontiers in Environmental Science, 2022)
The electricity crisis in Pakistan has been triggering grid power outages (load shedding) for many decades, which has not only affected the commercial and industrial sectors but also the domestic sector, specifically the livelihood of rural areas of the country. However, the extant literature advocates that renewable energy technologies (RETs), such as solar photovoltaic (PV) can be the remedy. Given the abundant availability of solar energy in Pakistan that can be converted into electrical energy using a solar PV system, this study examines the determinants of solar PV adoption in rural areas of Pakistan. Our preliminary investigations—using government/official publications—indicate that despite the huge potential of solar energy in Pakistan, the usage of solar PV systems at the household level in rural areas is still untapped, which makes this research agenda more appealing and provocative. In doing so, this study first conducts surveys, face-to-face comprehensive interviews, and questionnaires in four different districts of Pakistan and then implements a stepwise two-stage novel approach on a sample of 1,140 selected rural households. The first stage focuses on the determinants of solar PV system adoption, whereas the second stage focuses on the determinants of the type of solar PV system adopted. Using logistic regression, this study finds that age, education, children in school, income level, access to credit, gender (female), and price of a solar PV system are the factors significantly affecting the solar PV system adoption. In the second stage, we use a multivariate probit model and find that among these significant factors, the former five are significantly positive for the uptake of solar home-system, whereas the latter two are significant for both solar shed-lighting and solar panel-kit systems. In addition to these factors, landholding and access-to-road are significant for solar home systems, whereas household size, distance-to-market, and access-to-grid-electricity are significant for both solar shed-lighting and solar panel-kit systems. Since burning fossil fuels and solid biomass fuels for domestic energy needs are common in rural areas globally and cause carbon emissions and several severe health issues, the findings of this study are useful in many ways. In specific, we contribute to the literature examining the determinants of RETs in rural communities in developing countries.